Analysis Of Dynamic Capability Of Managers During The Covid-19 Pandemic Cooperative Village Units In The Mataraman Region, East Java - Sumantri, Bambang Agus; Adawiyah, Wiwiek Rabiatul; Banani, Ade (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research aim : to find out and identify dynamic capabilities by KUD managers during a pandemic and the results in the form of index values are used to determine the impact on KUD in Kediri and Madiun Residents and provide information in the form of strategies that must be carried out by KUD. Design/Methode/Approach : The variables in this study are latent or unobserved variables, namely variables that cannot be measured directly, but are formed through indicators observed through a questionnaire. The type of data used in this research consists of primary data and secondary data. the linkert scale developed in this study consists of 7. The data analysis technique used is descriptive statistical analysis using index numbers. Research Finding : dynamic capability, ability to acquire knowledge, ability to create knowledge, ability to combine knowledge, interpretation at 26.43 to 79.29 is in the low index category. Theoretical contribution/Originality : dynamic capabilities KUD in Indonesia. Practitionel/Policy implication : Dynamic capability has managerial implications that must be created, namely: first, KUD has very good business and non-business knowledge. Second, KUD has the ability to develop business, non-business and technology knowledge. And third, KUD has the ability to combine and or create business, non-business and technology knowledge. Research limitation : The research object has not been classified from the level of business size, type of business, and others so that it becomes a comparable comparison. Where research can be categorized into 3 strata, namely: large-scale KUD, medium-scale KUD and small-scale KUD. And each stratum is the focus of research because large, medium or small capabilities have different characteristics.